TEXTUAL REASON AND SOCIAL REFORM IN THE 19TH-CENTURY ISLAMIC RENEWAL MOVEMENT - Kholid, Nur; Shobaruddin, Dudin; Al Hanif, Furqon Mahmud; Budiyanto, Sigit (Jurnal Al-Ijtimaiyyah, 2025)
The 19th-century Islamic renewal movement emerged as a response to intellectual stagnation and colonial domination in the Muslim world. Reformists like Jamaluddin al-Afghani, Muhammad Abduh, and Rashid Rida advocated for a return to the Qur'an and Sunnah through rational and contextual interpretation—termed "textual reasoning"—rather than literalism. This study analyzes the relationship between this reasoning and social action, specifically concerning poverty alleviation and gender equality. Using a library research method with a social hermeneutic approach, the study finds that 19th-century reformism catalyzed practical transformations: educational reform, productive zakat management, and women's empowerment. The movement demonstrates Islam's capacity for sustainable social justice. This research offers a novel synthesis by linking theological "ijtihad" directly to socio-economic praxis, providing a framework for modern Muslim welfare.